Anteseden dan Konsekuensi dari Brand Attachment pada Mobile Banking - Shafa Fathiya (Peneliti.net, 2023)
The purpose of this study is to obtain related empirical evidence to analyze the positive influence of usability, security/privacy, interactivity on brand attachment, the positive influence of usability, security/privacy, interactivity on word of mouth, and the positive influence of brand attachment on word of mouth . The sampling technique in this study used purposive sampling with the criteria for respondents being individuals who are individual consumers as m-banking users. In this study using primary data obtained through a questionnaire created using Google Form and distributed to 207 respondents. The results of this study indicate that there is a positive influence of usability, security/privacy, interactivity on brand attachment, a positive influence of usability, security/privacy, interactivity on word of mouth, and a positive influence of brand attachment on word of mouth.